Use of Prosody and Information Structure in High Functioning Adults with Autism in Relation to Language Ability - DePape, Anne-Marie R.; Chen, Aoju; Hall, Geoffrey B.; Trainor, Laurel J. (Frontiers in Psychology, 2012)
Abnormal prosody is a striking feature of the speech of those with Autism Spectrum Disorder (ASD), but previous reports suggest large variability among those with ASD. Here we show that part of this heterogeneity can be explained by level of language functioning. We recorded semi-spontaneous but controlled conversations in adults with and without Autism Spectrum Disorder and measured features related to pitch and duration to determine (1) general use of prosodic features, (2) prosodic use in relation to marking information structure, specifically, the emphasis of new information in a sentence (focus) as opposed to information already given in the conversational context (topic), and (3) the relation between prosodic use and level of language function. We found that, compared to typical adults, those with ASD with high language functioning generally used a larger pitch range than controls but did not mark information structure, whereas those with moderate language functioning generally used a smaller pitch range than controls but marked information structure appropriately to a large extent. Both impaired general prosodic use and impaired marking of information structure would be expected to seriously impact social communication and thereby lead to increased difficulty in personal domains, such as making and keeping friendships, and in professional domains, such as competing for employment opportunities.